Distribution Factor Method Modified for Determine of Load Contribute based on the Power Factor in Transmission Line - Syarifuddin Nojeng; Syamsir Syamsir; Arif Jaya; Andi Syarifuddin; Mohammad Yusri Hassan (Institute of Advanced Engineering and Science, 2018)
This paper proposes a modification of distribution factor methods for identifying the load contribute in a transmission open access, with regard to the load power factor. This method may be considered as the first pricing strategy to be proposed in bilateral transaction for transmission usage, based on the actual use of the transmission network. The merit of this method relies on the existence of a load power factor with GLDF methods, which allocate the transmission cost, not only based on the amount of power flow but also on the load characteristic. A case study utilizing the IEEE 30-bus system was conducted to illustrate the contribution of the proposed method in allocating the transmission usage to the user in a fair manner.